الخطاب الاجتماعي في القرآن الكريم ومقاصده = Social discourse in the Holy Qur'an and its purposes = Wacana sosial dalam Al-Quran Al-Karim dan tujuannya - Elatrash, Radwan Jamal Yousef; Abeed, Sayyid Obaidillah (IIUM Press, International Islamic University Malaysia, 2020)
يتناول البحث حقيقة الخطاب الاجتماعي في القرآن الكريم، ويبرز أهميته باعتباره المعيار الذي يعيد التوازن بين الفرد والمجتمع الإنساني، وهو خطاب تفاعلي يُظهر هوية المجتمع، ويناقش مصالحه وهمومه وقضاياه ومفاهيمه ومدى تفاعلاته ومشاركاته في البناء الحضاري، فهو حديث عن تطبيق العدالة الاجتماعية بكلّ ما تعني الكلمة. ثم يتطرّق البحث إلى دراسة أمثلة له من الآيات القرآنية لإبراز بعض مقاصدها النبيلة، كما يشير إلى مخالفات ارتكبتها البشرية في ظلّ هيمنة الحضارة المادّية على الروحانية، ويثبت أخيراً أن الاهتداء بالقرآن ولا سيما فهم مقاصد خطابه الاجتماعي يُمهّد الطريق لإعادة التوازن بين الحياة المادية والدين، وبين الإنسان وأخيه الإنسان. وطبيعة البحث تقتضي أن تكون دراسةً تحليليةً لبعض نماذج الخطاب الاجتماعي في القرآن الكريم، ثم شرحها وتفسيرها في ضوء ما قاله المفسرون القدامى والمعاصرون. *************************************************************************** This research deals with the reality of the social discourse in the Holy Quran, and highlights its importance as the criterion that restores the balance between the individual and the human society. It is an interactive discourse that displays the identity of society and discusses its interests, concerns, issues, concepts and the extent of its interactions and participation in civilizational building development, It discusses the application of social justice in every sense of the word. Therefore, the study examines examples derived from Quranic verses to highlight some of its noble purposes, as well as the violations committed by humanity in light of the dominance of materialistic civilization over spiritual civilization, and finally proves their guidance by the Quran, especially understanding the purposes of its social speech paves the way to rebalance between material life and religion, and between humans. And the nature of this research requires that it should be an analytical study of some models of social discourse in the Holy Quran, and then explains and analyzes in the light of what the ancient and contemporary interpreters said. ****************************************************************************** Kajian tesis ini membincangkan tentang wacana kemasyarakatan dalam AlQuran AlKarim, ia menonjolkan kepentingannya sebagai kayu ukur yang mengimbangkan di antara seseorang dengan masyarakatnya. Ia adalah wacana interaktif yang menzahirkan identiti sesebuah masyarakat, dan membincangkan kepintingan, kebimbangan, persoalan, konsep sesbuah masyarakat dan sejauh mana jangkauan dan penglibatannya dalam pembinaan peradaban. Ia membicarakan tentang bagaimana keadilan masyarakat dapat diaplikasikan dengan sebenarbenarnya. Seterusnya kajian ini memaparkan contoh-contoh daripada ayat-ayat Al Quran untuk memperlihatkan maqasid atau fungsinya yang murni dan memperlihatkan pencabulan yang dilakukan oleh manusia akibat pengaruh tamadun duniawi mengatasi tamadun rohani dan akhirnya membuktikan bahawa dengan adanya panduan Al Quran dalam memahami wacana kemasyarakatan akan membawa ke arah pengimbangan semula di antara kehidupan material dengan agama, serta hubungan di antara sesama manusia. Oleh itu pendekatan kajian ini bersifat analitikal dengan menghuraikan contoh-contoh wacana kemasyarakatan dalam Al Quran AlKarim, kemudian menganalisisnya dan mentafsirkannya berpandukan kepada kajian ahli-ahli tafsir yang terdahulu dan yang kontemporari.